2005
DOI: 10.1007/s10194-005-0198-6
|View full text |Cite
|
Sign up to set email alerts
|

The Temperament and Character Inventory in women with migraine

Abstract: The purpose of this work was to investigate: (1) the differences in temperament and character between 49 women with migraine and 49 controls using the Temperament and Character Inventory (TCI), and (2) the extent to which these differences were related to migraine or to the presence of comorbid depression. The migraine patients scored significantly higher than the controls in two temperament dimensions—Harm Avoidance (HA) and Persistence (P)—and significantly lower in one character dimension—Self-Directedness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
21
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 10 publications
6
21
0
1
Order By: Relevance
“…Our migraine patients had higher scores in the HA scale than two different types of healthy controls. Our results are similar to earlier works of Di Piero et al and Mongini et al [6,25] using the TCI and consistent with other studies using other instruments such as the Dimensional Assessment of Personality Pathology [36]. It has been suggested that this scale (Harm Avoidance) indicates a heritable predisposition to form conditioned signals of punishment and frustrative nonreward.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our migraine patients had higher scores in the HA scale than two different types of healthy controls. Our results are similar to earlier works of Di Piero et al and Mongini et al [6,25] using the TCI and consistent with other studies using other instruments such as the Dimensional Assessment of Personality Pathology [36]. It has been suggested that this scale (Harm Avoidance) indicates a heritable predisposition to form conditioned signals of punishment and frustrative nonreward.…”
Section: Discussionsupporting
confidence: 93%
“…In a subsequent study Mongini et al [6] corroborated the presence of higher scores of HA in PWM compared with controls. Also the same study found higher scores of PE and lower scores of SD in PWM compared with controls [6]. On the other hand other studies have not shown the association of HA in PWM when it is controlled with the presence of depression measured with the Beck Depression Inventory, as Boz et al pointed out [26].…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations